Possibilities of applying organizational wellness programs - Trajkov, Marija T; Kljajić, Dragana; Grbić, Gordana; Šimpraga, Ljiljana (Education and Research in Health Sciences, 2022)
Globalization, industrialization, and information technology, along with extended seating, have caused many health problems for employees, from lifestyle-related diseases to musculoskeletal disorders to mental health problems. For most people, work is an important determinant of life that is necessary for the survival and well-being of an individual. On the other hand, a high degree of productivity, motivation and commitment of employees is important for the employer. Workplace health promotion plays an important role in achieving good employee health. The World Health Organization emphasizes that the workplace is a priority environment for the promotion of health and well-being, including the provision of a safe and healthy physical and psychosocial work environment. In developed countries, various approaches to health promotion have been implemented through organizational wellness programs for many years. However, there are a number of limiting factors for the implementation, efficiency and effectiveness of a wellness program in the workplace. This is especially true for countries that do not have a long tradition in implementing wellness programs. In accordance with the growing needs of our society for workplace wellness programs to be more represented, the aim of this paper is to point out the importance and need for the application, implementation and evaluation of wellness programs.
Keywords: workplace wellness programs; implementation; efficiency; effectiveness